Oscillatory behavior of a class of fractional difference equations with damping - Maria Selvam, George; Sagayaraj, Reni; Loganathan, Paul (International Journal of Applied Mathematical Research, 2014)
This paper investigates the oscillation of a class of fractional difference equations with damping term of the form   where denotes the Riemann-Liouville difference operator of order  is a quotient of odd positive integers. Based on a generalized Riccati transformation and some inequalities, we establish some sufficient conditions of oscillation criteria for it. Some applications are also presented for the established results.Keywords: Difference Equations, Oscillation, Fractional Order, Damping.